Association Between Weight-Adjusted Waist Index and Periodontitis: A Cross-Sectional Study and Mediation Analysis - Yang H; Lu Y; Zhao L; He Y; He Y; Chen D (Diabetes, Metabolic Syndrome and Obesity)
Hao Yang,1 Yayun Lu,2 Lina Zhao,3 Yufeng He,1 Yuecheng He,4 Dong Chen5,6 1Department of Stomatology, Health Examination Center of Shanghai Health and Medical Center, Huadong Sanatorium, Wuxi, People’s Republic of China; 2Nursing Department, Health Examination Center of Shanghai Health and Medical Center, Huadong Sanatorium, Wuxi, People’s Republic of China; 3Department of Stomatology, The Affiliated Hospital of Inner Mongolia Medical University, Inner Mongolia Medical University, Hohhot, People’s Republic of China; 4Department of Oral and Maxillofacial Implantology, Shanghai Ninth People’s Hospital, Shanghai, People’s Republic of China; 5Department of Endodontics, Shanghai Stomatological Hospital & School of Stomatology, Fudan University, Shanghai, People’s Republic of China; 6Shanghai Key Laboratory of Craniomaxillofacial Development and Diseases, Fudan University, Shanghai, People’s Republic of ChinaCorrespondence: Dong Chen, Department of Endodontics, Shanghai Stomatological Hospital & School of Stomatology, Fudan University, 356 East Beijing Road, Shanghai, 200001, People’s Republic of China, Email chendong@fudan.edu.cn Yufeng He, Department of Stomatology, Health Examination Center of Shanghai Health and Medical Center, Huadong Sanatorium, Wuxi, 214065, People’s Republic of China, Email 1721671899@qq.comAim: The research examined the correlation between the weight-adjusted waist index (WWI) and periodontal disease, as well as the intermediary influence of triglyceride glucose (TyG) index-related indicators, utilizing a health examination dataset.Methods: This cross-sectional study included 39,522 subjects from health check-up database of Shanghai Health and Medical Center. The WWI was determined by applying a formula that includes dividing the waist circumference (WC) by the body weight’s square root. Periodontitis diagnosis followed the Centers for Disease Control and Prevention and American Academy of Periodontology (CDC/AAP) classification. The correlation between the WWI and periodontitis was investigated through multivariate logistic regression and smoothing curve fitting. Subgroup analysis and interaction tests were also performed to verify the stability of the results. A mediation analysis was conducted to quantify the direct and indirect influences mediated by the TyG-related indicators [TyG, TyG -body mass index (TyG-BMI), TyG -waist-to-height ratio (TyG-WHtR), and TyG-waist circumference (TyG-WC)].Results: Multivariable logistic regression analysis revealed the positive association of WWI and periodontitis (OR=1.37, 95% CI: 1.30– 1.43). Compared to those in the lowest quartile of WWI, participants in the highest quartile exhibited a 82% higher likelihood of periodontitis (OR=1.82, 95% CI: 1.69– 1.96). Subgroup analysis and interaction tests revealed that this positive correlation was consistent in gender, BMI, WC, smoking, drinking, hypertension, and dyslipidemia (P for interaction > 0.05), with some variations noted by age and diabetes status (P for interaction< 0.05). Mediation analysis showed that the proportions mediated by TyG, TyG-BMI, TyG-WC, and TyG-WHtR on the association of WWI and periodontitis risk were 13.13%, 6.30%, 16.46% and 19.79%, respectively.Conclusion: A higher WWI in Chinese adults was linked to an increased likelihood of periodontitis, and this correlation could be partially explained by elevated levels of TyG index-related indicators.Keywords: weight-adjusted waist index, periodontitis, triglyceride glucose index, mediating effect